Population Attributable Fraction of Nonvaccination of Child and Adolescent Vaccines Attributed to Parental Vaccine Hesitancy, 2018–2019. Issue 9 (15th March 2022) - Nguyen, Kimberly H; Srivastav, Anup; Vaish, Akhil; Singleton, James A
Abstract: Understanding the role of vaccine hesitancy in undervaccination or nonvaccination of childhood vaccines is important for increasing vaccine confidence and uptake. We used data from April to June interviews in the 2018 and 2019 National Immunization Survey–Flu ( n = 78, 725, United States), a nationally representative cross-sectional household cellular telephone survey. We determined the adjusted population attributable fraction (PAF) for each recommended childhood vaccine to assess the contribution of vaccine hesitancy to the observed nonvaccination level. Hesitancy is defined as being somewhat or very hesitant toward childhood vaccines. Furthermore, we assessed the PAF of nonvaccination for influenza according to sociodemographic characteristics, Department of Health and Human Services region, and state. The proportion of nonvaccination attributed to parental vaccine hesitancy was lowest for hepatitis B birth dose vaccine (6.5%) and highest for ≥3-dose diphtheria and tetanus toxoids and acellular pertussis vaccine (31.3%). The PAF of influenza nonvaccination was highest for non-Hispanic Black populations (15.4%), households with high educational (17.7%) and income (16.5%) levels, and urban areas (16.1%). Among states, PAF ranged from 25.4% (New Hampshire) to 7.5% (Louisiana). Implementing strategies to increase vaccination confidence and uptake are important, particularly during the coronavirus disease 2019 pandemic.